Caracterización de compuestos fenólicos y actividad antioxidante de extractos hidroalcohólicos, infuso de decocto de Prosopis pallida - Suárez Rebaza, Luz Angélica (2019)
ABSTRACT The fruits of the "algarrobo" contain phenolic compounds (PC) to which important nutraceutical properties are attributed. The objective was to characterize the phenolic compound with greater abundance and to determine the antioxidant activity (AA) in five extracts (45%, 70%, 96% ethanol, infusion and decoction) of fruits of Prosopis pallida (Humb. & Bonpl. Ex Willd.) Kunth of the regions of Tumbes, Piura, Lambayeque and La Libertad. The PC were quantified by the Folin-Ciocalteu method and the AA was evaluated by the DPPH, FRAP and ABTS methods. The best extract with PC was ethanol 96% of the fruits of Piura with 58.03±2.50 mg Gallic acid equivalents/g (GAE/g). The AA fluctuated between 5.27±0.30-2.12±0.08, 8.46±0.45-5.32±0.34 and 17.63±0.53-11.16±0.29 mg of Trolox equivalents/g, for DPPH, FRAP and ABTS, respectively in the unpurified samples. While, among the purified extracts, the decoction of La Libertad showed higher concentration of PC (90.65±1.70 mg GAE/g) and higher AA by the methods of DPPH, FRAP and ABTS. On the other hand, the phenolic compound of higher concentration and with antioxidant activity was characterized by liquid chromatography coupled to mass spectrometry, elucidating its corresponding structure and general formula C27H31O15. It is concluded that the phenolic compound of higher concentration with AA is Apigenin-6,8-digalactoside (vicenin) and belongs to the flavones.